SINERGI APLIKASI CANVA MELALUI VIDEO PEMBELAJARAN POWTOON MATERI MITIGASI BENCANA ALAM KELAS XI IPS SMAN 8 PADANG - Azizah, Devrina Nur; Rahmanelli, Rahmanelli (JURNAL BUANA, 2023)
This study aims to determine the feasibility of the synergy of the Canva application through the development of powtoon learning video media for natural disaster mitigation material in class XI IPS SMAN 8 Padang. This research method is Research and Development R&D with a 4-D development model consisting of define, design, development, and disseminate. The population of class XI IPS SMAN 8 Padang amounted to 119 students, the sample of class XI IPS 1 amounted to 31 students. Sample consideration techniques using purposive sampling, data collection through observation, test interviews for Likert scale questionnaire data analysis. The results of this study obtained scores and percentages: 1) decent material experts (2.91 77%), 2) very decent media experts (4.0 100%), 3) very decent linguists (3.91 98%), 4) assessment by teachers (3.28 82%), class XI social studies assessment 1 obtained very decent (3.53 84%). The acquisition of the decent category in this case can be proven through the results of UH class XI IPS 1 increased by 60%, previously the average value was 49.90 to 82.80 a difference of 30.9. Keywords : Synergy, Canva, Powtoon, Learning Media